1992
DOI: 10.1037/0033-2909.111.2.347
|View full text |Cite
|
Sign up to set email alerts
|

Temperature, aggression, and the negative affect escape model.

Abstract: This article addresses Bell's (1992) comments on Anderson's (1989) review of the temperature-aggression literature. At a global level, all agree that geographic region studies and most time period studies do not cleanly address the question of the functional shape relating temperature to aggression. In addition, all agree that the negative affect escape model warrants additional empirical investigation. At a more specific level, however, numerous inaccuracies and misinterpretations are noted and corrected. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Others have also noted relations between temperature and Meteorology, affect and behavior 389 behaviors (for example, Goldstein, 1972;Baron, 1977;Persinger, 1980;Sanders & Brizzolara, 1982;Whitton et al, 1982;Cohn, 1990a;Anderson & DeNeve, 1992;Barker et al, 1994). However, the majority of findings seem to suggest that rises in temperature are paired with aggressive acts and crime-related behaviors.…”
Section: Weather and Social Outcomesmentioning
confidence: 88%
“…Others have also noted relations between temperature and Meteorology, affect and behavior 389 behaviors (for example, Goldstein, 1972;Baron, 1977;Persinger, 1980;Sanders & Brizzolara, 1982;Whitton et al, 1982;Cohn, 1990a;Anderson & DeNeve, 1992;Barker et al, 1994). However, the majority of findings seem to suggest that rises in temperature are paired with aggressive acts and crime-related behaviors.…”
Section: Weather and Social Outcomesmentioning
confidence: 88%
“…Anderson & DeNeve, 1992). Field studies using police and weather office records have found virtually no evidence of a downturn in aggression at extremely high temperatures (e.g., c.A.…”
Section: When the Action Heats Upmentioning
confidence: 99%
“…In both laboratory experiments and field studies within nations, a general temperature-aggression link is well-documented (e.g., Anderson, 1987;Anderson & Anderson, 1996;Geen, 1990; Goldstein, 1994;Rotton, 1986), although there is an ongoing debate about whether the relation is rectilinear (Anderson, 1989;Anderson & DeNeve, 1992;Anderson, Deuser, & DeNeve, 1995) or curvilinear in the shape of an inverted U (Baron & Bell, 1976;Bell, 1992). However, because this literature primarily applies to affect-based, spontaneous aggression at the individual level (Anderson, 1989;Anderson & DeNeve, 1992), it does not provide potential explanations for mass violence that is primarily government-related, society-based, and planned.The evidence for a specific association between ambient temperature and organized political violence rests solely on a 51-nation study by D. C. Schwartz (1968). He reported that, from 1948 to 1964, the frequency of coups, assassinations, terrorism, guerilla wars, and revolts covaried with mean annual temperature in a curvilinear way.…”
mentioning
confidence: 99%